1995
DOI: 10.1080/00288233.1995.9513110
|View full text |Cite
|
Sign up to set email alerts
|

Single trait selection for yearling fleece weight or liveweight in Romney sheep—direct responses

Abstract: An experiment was carried out to study the responses to selection for yearling fleece weight and liveweight in Romney sheep. There were two selection lines, one selected for fleece weight (FW) and the other for liveweight (LW), and a control (CO) line was maintained. Data from lambs born 1967-90 were analysed to quantify the direct responses to selection. By 1990 there had been an average of 9 generations of selection with an average generation interval of 2.7 years. Realised heritabilities and selection respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The HF flock had significantly higher wool growth in winter by 32 and 37% in adult ewes and hogget respectively compared with CR (Wuliji et al, 1995). Heritability estimates for live weights, fleece weight and wool characteristics were in agreement with the reports of Baker et al (1979), Clarke and Rae (1977), Johnson et al (1995), Clarke et al (1995), and the earlier estimates of the flocks (Wuliji et al, 1991).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The HF flock had significantly higher wool growth in winter by 32 and 37% in adult ewes and hogget respectively compared with CR (Wuliji et al, 1995). Heritability estimates for live weights, fleece weight and wool characteristics were in agreement with the reports of Baker et al (1979), Clarke and Rae (1977), Johnson et al (1995), Clarke et al (1995), and the earlier estimates of the flocks (Wuliji et al, 1991).…”
Section: Discussionsupporting
confidence: 89%
“…He predicted the genetic improvement in a crossbred wool flock of 200 breeding ewes, subject to single trait selection, to be 0.192 kg fleece weight per generation, which was 0.064 kg/year. The average yearly response in fleece weight since establishment in 3 other comparable fleece weight selection Romney flocks in NZ were 0.034 kg in the Massey University line (established in 1956;Blair et al, 1985), 0.047 kg in the Tokanui line (established in 1967;Johnson et al, 1995), and 0.065 kg in the Woodlands line (established in 1973;. Those flocks were selected for a similar environment, flock sizes and selection intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thompson & Juga (1989) showed that the method of Newman et al (1973) is biased downwards as a result of a reduction in variance due to linkage disequilibrium (Bulmer, 1971) and proposed a recursive method to estimate realized heritabilities. Reporting on a selection experiment with sheep, Johnson et al (1995) found lowest realized heritabilities estimated by the method of Newman et al (1973) followed by those estimated using the method of Thompson & Juga (1989) which were similar to, but still lower than, the REML estimates. The low selection response for weaning weight was due to the low REML heritability estimate which was influenced by the presence of sire x year interaction (Beffa et al, 2009b).…”
Section: Resultsmentioning
confidence: 99%
“…The low selection response for weaning weight was due to the low REML heritability estimate which was influenced by the presence of sire x year interaction (Beffa et al, 2009b). In theory, REML techniques using an animal model and complete relationship matrix yield unbiased estimated of base population parameters (Johnson et al, 1995). However, Meyer & Hill (1991) found that REML analyses did not account for a decrease in genetic variance in the analyses of 23 generations of selection in mice.…”
Section: Resultsmentioning
confidence: 99%